2017
DOI: 10.1038/cddis.2017.420
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium abscessus glycopeptidolipids inhibit macrophage apoptosis and bacterial spreading by targeting mitochondrial cyclophilin D

Abstract: Mycobacterium abscessus (MAB) is a species of nontuberculous mycobacteria (NTM) and a major causative pathogen of pulmonary diseases especially in patients with cystic fibrosis. MAB infection is notoriously difficult to treat because of its intrinsic or inducible resistance to most antibiotics. The rough (R) morphotype of MAB, lacking cell surface glycopeptidolipids (GPLs), is associated with more severe and persistent infection than the smooth (S) type; however, the mechanisms underlying the R type’s virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 45 publications
(52 reference statements)
2
54
0
Order By: Relevance
“…However, we recently showed, by looking at the differential intracellular behavior of both S and R M. abscessus variants, that GPLs confer a clear intracellular survival advantage to the S variant compared with the R variant, including resistance to several cellular antibacterial mechanisms, such as blockage of phagosomal acidification, and resistance to apoptosis and autophagy (4,7). Complementary to our study, GPLs were shown to inhibit apoptosis in M. abscessus-infected MΦ by interacting with the mitochondrial cyclophilin D (29).…”
Section: Significancesupporting
confidence: 79%
“…However, we recently showed, by looking at the differential intracellular behavior of both S and R M. abscessus variants, that GPLs confer a clear intracellular survival advantage to the S variant compared with the R variant, including resistance to several cellular antibacterial mechanisms, such as blockage of phagosomal acidification, and resistance to apoptosis and autophagy (4,7). Complementary to our study, GPLs were shown to inhibit apoptosis in M. abscessus-infected MΦ by interacting with the mitochondrial cyclophilin D (29).…”
Section: Significancesupporting
confidence: 79%
“…The role apoptosis plays in NTM-infected macrophages is controversial since both host-protection (Fratazzi et al, 1997;Bai et al, 2011b) and NTM survival (Early et al, 2011;Bermudez et al, 2015;Whang et al, 2017) have been implicated with apoptosis. Compared to M. smegmatis and other NTM, MTB H37Rv induced the least amount of apoptosis as evinced by lower number of TUNEL-positive cells as well as lower expression of annexin-V, cytochrome C, Bax, and Bak.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of Mycobacterium tuberculosis (MTB)infected macrophages have been associated with either favoring the host through the killing of intracellular bacteria (Keane et al, 1997;Rojas et al, 1997;Keane et al, 2002) or benefiting MTB via their escape from the dying cells to infect neighboring cells (Aguilo et al, 2013;Augenstreich et al, 2017). By similar mechanisms, both salubrious (Fratazzi et al, 1997;Bai et al, 2011b) and deleterious (Early et al, 2011;Bermudez et al, 2015;Whang et al, 2017) effect of apoptosis to host cells have been implicated with NTM infection. Compared to NTM, MTB is considered to possess greater virulence due to its increased ability to subvert the host immune response.…”
Section: Introductionmentioning
confidence: 99%
“…It can thus be inferred either (i) that GPLs are essentially localized within clusters on the M. abscessus S surface rather than being homogenously distributed all over the bacilli or (ii) that the different classes of GPLs, i.e. diglycosylated (less hydrophilic head group) and triglycosylated (more hydrophilic head group) GPLs, 21 define nanodomains of varying hydrophobicity. To test either of these hypotheses would ultimately require a technique allowing to specifically probe GPLs, including different classes of GPLs that would rely on anti-GPL antibodies specific for each class of GPL (currently unavailable) or on specific mutants lacking either form of GPL.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] During infection of macrophages S variants suppress phagosomal acidification as well as apoptosis. 20,21 On the other hand, R variants, which are almost exclusively isolated from infected patients, do not block phagosomal acidification or apoptosis, causing the death and lysis of their host macrophages and consequentially their release into the extracellular environment. 20,22 They hyper aggregate and hence organize as they grow into serpentine cord-like structuresseen both in vitro ( Fig.…”
Section: Introductionmentioning
confidence: 99%